High Voltage, Transition Metal Complex Enables Efficient Electrochemical Energy Storage in a Li‐Ion Battery Full Cell. (7th December 2016) - Zheng, Qi; Niu, Zhihui; Ye, Jing; Zhang, Shun; Zhang, Luwei; Li, Lixing; Zhao, Yu; Zhang, Xiaohong
Abstract : Efficient energy storage systems impact profoundly the renewable energy future. The performance of current electrical energy storage technologies falls well short of requirements for using electrical energy efficiently in transportation, commercial, and residential applications. This paper explores the possibility by using transition‐metal‐based complexes as active materials in a Li‐ion battery full cell that synergizes the concept of both lithium‐ion batteries and redox flow batteries. A cathode made from transition metal complex, [Fe(bpy)3 ](BF4 )2, exhibits high discharge voltage approaching 4 V (vs Li/Li + ). When coupled with a Li4 Ti5 O12 anode, the Li‐ion full battery exhibits a cell voltage exceeding 2.2 V and decent cycling efficiencies with Coulombic efficiency and energy/voltage efficiencies above 99% and 92%/93%, respectively. Such a Li‐ion battery full cell offers distinct features such as low cost and flexibility in molecular structure design. The result reveals a generic design route toward iron‐based complexes as cathode materials with good electrochemical performances. Abstract : By suitable choice of ligand, the formal redox potential of transition metal complex can be shifted in the desired direction with improved characteristics such as structural stability and redox kinetics. A Li‐ion battery full cell constructed from such complex exhibits stable working potential exceeding 2 V and decent cycling efficiencies.